THE CONDITIONAL TENSE (SYNAPSES: INSIGHTS ACROSS THE DISCIPLINES, 2025)
This article provides comprehensive and clear information about an important topic in the Italian language — the conditional tense, which is one of the main verb moods and is especially essential for formal communication. The conditional tense has similarities to the conditional–optative mood in the Uzbek language. The topic is explained through examples, explanations, and comparisons.